Cultural Value of Cassava Food as a Tourism Attraction in Cireundeu Traditional Village - Rahmat Priyanto; Gita Desmafianti (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2023)
This study aims to describe the cultural value of cassava food as an attraction for tourists visiting the Cireundeu Traditional Village. The method used in this study is a qualitative method with a descriptive approach. Research data sources consist of primary data sources, namely from research data obtained through observation activities, interviews, and documentation directly to the field, while secondary data are obtained through literature studies related to the study. The results showed that the cultural value of cassava food in Cireundeu Traditional Village was divided into 3 parts, including cultural values regarding symbols related to cassava food, behavior related to cassava food, and embedded beliefs related to cassava food. The results of the next study explained the attractiveness of cassava food in the Cireundeu Traditional Village through the point of view of its cultural uniqueness, then originality, authenticity and diversity. From the results of this study, it is hoped that it can provide input for managers or all elements in the Ciruendeu Traditional Village in order to develop cassava food culture into a leading tourist attraction in Cimahi City.